Pengaruh Debt to Asset Ratio terhadap Return On Equity Pada Usaha Nani Collection Sibolga - Yohana Defi Sartika Luahambowo; Yusi Tri Utari Panggabean (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
This study analyzes the effect of Debt to Asset Ratio (DAR) on Return on Equity (ROE) at Nani Collection Sibolga using a quantitative descriptive correlational approach. Secondary financial statement data from 2020–2024 were analyzed using SPSS, including classical assumption tests, simple linear regression, and t-tests. The results show a positive but low correlation (r = 0.258) between DAR and ROE, with an insignificant effect (p = 0.675) and DAR contributing only 6.7% to ROE. These findings indicate that other factors play a more dominant role in determining the profitability of SMEs. Therefore, managing capital structure should be complemented by strategies such as improving operational efficiency and sales volume to enhance ROE.